Penerapan Metode Demonstrasi Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Shalat Jenazah di SMA Islam Ibnu Rusyd Kotabumi Tahun Ajaran 2023/2024 - Solihin, Ahmad; Kurniawan, Muchlis; Patimah, Siti; Ali, M Makhrus; Arafah, A Latief Arung (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
Choosing the right choice in applying learning methods is an important factor in the success of learning activities. Islamic religious education teachers choose demonstration learning methods to be applied so that all learning objectives for the practice of funeral prayers can be achieved optimally. This research aims to (1) to find out how Islamic religious education teachers apply the demonstration method to material on the practice of funeral prayers, (2) to find out the obstacles faced by Islamic religious education teachers in applying the demonstration method to funeral prayer material. The data collection technique uses interviews, observation and documentation. The data analysis used is data reduction, data presentation and verification. Based on the results of data analysis, the following results were obtained: 1). Application of the demonstration method to improve learning outcomes regarding funeral prayer material, namely opening activities, core activities and closing activities,2). The obstacles faced by Islamic Religious Education teachers in implementing the demonstration method on the material on funeral prayers are the lack of time, students being busy themselves, and the lack of adequate facilities and infrastructure.